Ungkapan Bermakna Budaya pada Upacara Adat - Tomasoa, Herlina (Kajian Linguistik, 2015)
This study aims to explain the process of Cuci Negeri Soyacustomary ceremony, to identify the type of language expression and to analyzethe language expression dan cultural meaning in customary ceremony as well asto explain of Soya society`s mindset based on cultural meaning in languageexpression in Soya customary ceremony. This study was conducted in Soyavillage, located in Ambon city which still used tana language. This study usedqualitative descriptive method. The data is collected by using interviewtechnique and analyzed by Miles and Huberman model data analysis, such as datareduction, data display, and data conclusion. The results show that thelanguage expressions found in Cuci Negeri Soya is kapata which delivered by thecustom head and 8 songs sung by the member of customary ceremony. From thoselanguage expression, it was identified 12 language expression containingcultural meaning which categorized to some types of expression. The types ofexpression consist of 1 greeting expression, 2 respect expressions, 4 prayexpressions, 2 advise expressions and information expression. The mindset ofSoya society in language expression has positive values in life in general andhousehold, has a religious nature, helping each other, courtesy, mutual respectand always give priority to the sanctity.Â Keywords:Language expression, cultural meaning, Customary Ceremony of Cuci Negeri Soya